APLIKASI PASURUAN CITY GUIDE BERBASIS ANDROID DENGAN MENGGUNAKAN METODE LBS (LOCATION BASED SERVICE) - Sigit Riyadi; Muhammad Afif (STMIK YADIKA BANGIL, 2021)
Abstract: Smart City is a term in assessing a City that has succeeded in utilizing Information Technology as a means of supporting the government and the community in providing facilities and services. Based on the SmartCity concept, an Android-based